PENGARUH PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Ilyas Riski; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to examine partial and simultaneous the influence of company growth and capital structure on corporate value. Where independent variable in this research is the growth of the company and capital structure, while dependent variable is company value. The sample used is secondary data derived from the financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange in 2011-2015. Sampling method used purposive sampling. The sample used is 7 companies. Data analysis techniques used are simple linear regression and multiple linear regression. The results of the research partially indicate that the company's growth has a significant negative effect on corporate value and the capital structure has a positive and significant effect on corporate value. While simultaneously company growth and capital structure have a positive and significant effect on corporate value.Key Words : company growth, capital structure, corporate value